Innovations in Distribution Logistics - Nunen, Jo A.E.E.; Speranza, M. Grazia.; Bertazzi, Luca. (Lecture Notes in Economics and Mathematical Systems, 2009)
In a globalized economy logistics has become a crucial area for the success of companies. The performance of each company depends on the performance of its suppliers and of its business partners. The customers of each company are spread on a large geographical space. For this reason distribution logistics is the most important and complex part of logistics. An efficient and effective management of distribution logistics is a key issue for the success of a company. There are many different problems to deal with, from facility location to transportation, to inventory management, and, most important, to the integration and optimization of the entire logistics network. Quantitative methods provide relevant tools to support decisions, from strategic to operational, in distribution logistics.